ANALYSIS AND PROCESS MANAGEMENT OF OUTDOOR LIGHTING SYSTEM INSTALLATION TO REDUCE INSTALLATION COST - Pornpojratanakul, Vinai; Bunjongjit, Sulee (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research aims to develop installation process for outdoor lighting system to attain high efficiency, low cost and reliable installation. The original exterior lighting circuit design has high cost and low load in each sub-circuit. In addition, the damage to materials in the construction period, such as wires, conduits, trees in the garden, lamps, which are all caused by excavation, whether digging to install conduits or digging to move garden trees may occur. The methodology aims to reduce cost without any impact on number, position, and load of the outdoor lighting. The new design considers the voltage drop on each sub circuit to improved efficient and reduce damage to equipment materials by rearrange the working sequence between electrical system and landscape architecture. The result from implementation proposed process demonstrated that material usage can be reduced up to 30.13% and cost reduction by 28.58%, which is significant for project management.